Peningkatan Kemampuan Literasi Numerasi Siswa SDN 1 Pedes Melalui Program Bimbel Intensif - Arie Purwanto; Nanang Khuzaini; Nuryadi; Rusmining; Nafida Hetty Marhaeni; Muhammad Irfan Rumasoreng; Naela Faza Fariha (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Service Program (PkM) aims to improve the numeracy literacy skills of students at SD Negeri 1 Pedes through intensive tutoring at the UMBY Mathematics Education Tutoring Center "The Brilliant Minds". This activity was conducted from June to July 2026, targeting 3rd grade students. The program was implemented through an academic collaboration between Mathematics Education lecturers from Universitas Mercu Buana Yogyakarta (UMBY), Mathematics Education lecturers from Universitas Ahmad Dahlan (UAD), and students from the UMBY Mathematics Education Student Association (HIMATIKA). The implementation method was based on a need assessment and a participatory approach comprising five stages: preparation, diagnostic assessment, module/tool development, intensive tutoring, and evaluation and follow-up. One of the main innovations applied by student tutors was the use of the Jarimatika method and context-based word problems to reduce math anxiety and enhance students' concrete understanding. The evaluation results showed an increase in the overall average numeracy score, from a pretest score of 93.45 to a posttest score of 95.00. The most significant improvement was experienced by students in the category requiring intensive guidance. This program proved effective in building students' motivation, confidence, and critical thinking skills, while providing a sustainable impact through the handover of learning modules to the partner school.